Quantitative structure - activity relationship : - Dastmalchi, Siavoush (CRC Press, Taylor & Francis Group, 2018)
Quantitative Structure – Activity Relationship: A Practical Approach provides a detailed overview of computational approaches in QSAR studies. It covers the applications of different algorithms in various steps of a QSAR analysis and shows clear examples. Each chapter introduces the tools and software involved. Moreover, challenges and issues which may be faced in any step of the analysis are thoroughly broken down based on the OECD guidelines, enabling the reader to familiarize themselves with potential end results.